1983
DOI: 10.1084/jem.158.2.529
|View full text |Cite
|
Sign up to set email alerts
|

Induction of rheumatoid antibodies in the mouse. Regulated production of autoantibody in the secondary humoral response.

Abstract: A/J mice were found to produce autoreactive IgM anti-IgG1 in response to secondary immunization with a number of protein antigens. No anti-IgG1 was produced after a single such immunization, indicating that antigen: IgG1 antibody complexes were responsible for inducing the autoreactive response. The size of the anti-IgG1 response was in some cases massive and of the same order of magnitude as the response to the foreign immunizing material. No significant anti-IgG2a, anti-IgG2b, or anti-IgG3 response was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
3

Year Published

1987
1987
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(63 citation statements)
references
References 32 publications
3
57
0
3
Order By: Relevance
“…The latter will thus become the selected B cell target for T cell help. This mechanism explains the negative feedback of antibody on the antibody response (10) and, in addition, the transient production of RF in the secondary immune response or upon immunization with immune complexes (11)(12)(13) .…”
Section: Discussionmentioning
confidence: 95%
“…The latter will thus become the selected B cell target for T cell help. This mechanism explains the negative feedback of antibody on the antibody response (10) and, in addition, the transient production of RF in the secondary immune response or upon immunization with immune complexes (11)(12)(13) .…”
Section: Discussionmentioning
confidence: 95%
“…The (26)(27)(28)(29)(30). These autoantibodies are produced by 3-20% of murine hybridomas derived from LPS-stimulated splenic B cells (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that the IgM RF production can be induced following antigenic stimulation, likely through the activation of low-affinity RF-specific B cells by IC [3,4]. Highaffinity RF-specific B cells of the IgG isotype generated during the germinal center response are likely to be efficiently eliminated by apoptosis through interaction with excess amounts of monomeric IgG.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that IgM RF can be formed spontaneously [1] and following mitogenic or antigenic stimulation in non-autoimmune strains of mice [2][3][4]. RF formed in non-autoimmune mice are nearly always restricted to the IgM class, while lupusprone MRL-lpr/lpr mice deficient in the Fas apoptosis receptor spontaneously produce high titers of IgG RF as well as IgM RF [5][6][7].…”
Section: Introductionmentioning
confidence: 99%